Design an efficient internet of things data compression for healthcare applications - Ahmed Najah Kahdim; Mehdi Ebady Manaa (Institute of Advanced Engineering and Science, 2022)
The internet of things (IoT) is an ecosystem of connected objects that are accessible and available through the internet. This